2008
DOI: 10.1177/1933719108324171
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol Mediates Apoptosis Through Caspase-Dependent and Independent Mechanisms in Ovarian Cancer Cells But Not in Normal Counterparts

Abstract: 2-Methoxyestradiol, alone or in combination with tumor necrosis factor-related apoptosis-inducing ligand, should be considered as a potential treatment for ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
0
20
1
Order By: Relevance
“…The induction of superoxide or its conversion into H 2 O 2 has been implicated as the mechanism through which 2ME2 exerts cytotoxicity (11)(12)(13). We therefore determined the effect of 2ME2 analogues on cellular superoxide concentrations by measuring the superoxide-dependent oxidation of the fluorescent dye dihydroethidium.…”
Section: Effects Of 2me2 Analogues On Chromatin Condensationmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of superoxide or its conversion into H 2 O 2 has been implicated as the mechanism through which 2ME2 exerts cytotoxicity (11)(12)(13). We therefore determined the effect of 2ME2 analogues on cellular superoxide concentrations by measuring the superoxide-dependent oxidation of the fluorescent dye dihydroethidium.…”
Section: Effects Of 2me2 Analogues On Chromatin Condensationmentioning
confidence: 99%
“…In addition to the inhibition of microtubule dynamics and induction of cell cycle arrest, the proapoptotic action of 2ME2 has also been linked to the stimulation of cellular reactive oxygen species (ROS) production, resulting in the release of cytochrome c from the mitochondria and activation of caspases (8)(9)(10)(11)(12)(13). Specifically, 2ME2 has been reported to inhibit superoxide dismutase enzymes (8).…”
Section: Introductionmentioning
confidence: 99%
“…MCF-12A cells) is not. Also the comparison between primary cultures of normal cells and cancerous ovarian epithelium revealed that only the latter cells are sensitive to 2-ME (Kato et al 2008). Next, we demonstrated that 2-ME displays a dose-dependent effect on cell cycle, leading to the accumulation of cells in G 2 /M characterized by the presence of phosphorylated-H3 histone.…”
Section: Discussionmentioning
confidence: 66%
“…In fact, given that drug resistance of cancer cells is often correlated with the evasion of apoptosis, a major goal in cancer research is to selectively increase the susceptibility of cancer cells to apoptosis-based strategies (Giansanti and Scovassi 2008). Previous studies have reported the ability of 2-ME to induce apoptosis in various human cancer cell lines, by triggering both the extrinsic (Pribluda et al 2000;LaValle et al 2003;Mooberry et al 2003;Shimada et al 2004;Kato et al 2008;Thaver et al 2009) and intrinsic pathway (Yue et al 1997;Attalla et al 1998, Schumacher andNeuhaus 2001;Bu et al 2002;Mooberry 2003;Shimada et al 2003;Gao et al 2005;Zou et al 2006;Fukui and Zhu 2009). The activation of caspase-independent apoptosis by 2-ME has also been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation